Human Resource Information Systems: Basics, Applications, and Future Directions New Edition Available : Basics, Applications, and Future Directions - Johnson, Richard D.; Carlson, Kevin D.; Kavanagh, Michael J. (SAGE Publications, Inc. (US), 2020)
Human Resource Information Systems: Basics, Applications, and Future Directions is a one-of-a-kind book that provides a thorough introduction to the field of Human Resource Information Systems (HRIS) and shows how organizations today can leverage HRIS to make better people decisions and manage talent more effectively. Unlike other texts that overwhelm students with technical information and jargon, this revised Fifth Edition offers a balanced approach in dealing with HR issues and IT/IS issues by drawing from experts in both areas. It includes the latest research and developments in the areas of HRIS justification strategies, HR technology, big data, and artificial intelligence. Numerous examples, best practices, discussion questions, and case studies, make this book the most student-friendly and current text on the market.   Included with this title: The password-protected Instructor Resource Site (formally known as SAGE Edge) offers access to all text-specific resources, including a test bank and editable, chapter-specific PowerPoint® slides.